An Epidemiological Study of Thiopurinemethyltransferase Variants in a Croatian Inflammatory Bowel Disease Patient Cohort - Agata Ladić; Nada Božina; Vladimir Borzan; Marko Brinar; Boris Vucelić; Silvija Čuković-Čavka (Acta Clinica Croatica, 2016)
Thiopurine S-methyltransferase (TPMT) is an enzyme that converts thiopurine drugs into inactive metabolites. Over 20 variant TPMT-encoding alleles, which cause reduced enzymatic activity, have been discovered so far. Our aim was to investigate the frequencies of variant alleles, i.e. genotypes in inflammatory bowel disease (IBD) patients and healthy individuals and to compare these frequencies with selected world populations. The most common variant alleles TPMT*2, TPMT*3A, TPMT*3B and TPMT*3C were analyzed with polymerase chain reactionbased assays and allele-specific polymerase chain reaction-based assays in 685 participants including 459 IBD patients and 226 healthy volunteers. Study results revealed 434/459 (94.55%) IBD patients and 213/226 (94.25%) healthy subjects to be homozygous for the wild-type allele (TPMT*1/*1). TPMT*1/*2 and TPMT *1/*3C genotypes were found in 4/459 (0.87%) and 7/459 (1.53%) IBD patients, respectively; in healthy volunteers they were not found. TPMT*1/*3A genotype was found in 14/459 (3.05%) IBD patients and 13/226 (5.75%) healthy subjects. Variant genotypes were statistically significantly more common in Crohn’s disease subgroup than in ulcerative colitis subgroup. The prevalence of variant genotypes was 23/338 (6.80%) in Crohn’s disease subgroup as compared with 2/121 (1.65%) in ulcerative colitis subgroup (χ2=4.59; p=0.032). In conclusion, the most frequently occurring nonfunctional TPMT allele in Croatian population is TPMT*3A. The overall frequency of mutant alleles in our population is statistically nonsignificantly lower when compared with other populations of Caucasian origin. The Crohn’s disease group had more mutant alleles than the ulcerative colitis group.